Respuesta :

Solution:

[tex] \sqrt{3} x + 4 - 2 = 3 \\ = > \sqrt{3} x = 3 - 4 + 2 \\ = > \sqrt{3} x = 1 \\ = > x = \frac{1}{ \sqrt{3} } \\rationalising \: \: \: the \: \: \: denominator \\ = > x = \frac{1}{ \sqrt{3} } \times \frac{ \sqrt{3} }{ \sqrt{3} } \\ = > x = \frac{ \sqrt{3} }{3} \\ [/tex]

Answer:

[tex] \frac{ \sqrt{3} }{3} [/tex]

Answer: x = 7

Step-by-step explanation:

[tex]\sqrt{3x+4}=3+2[/tex]

[tex]\sqrt{3x+4}=5[/tex]

[tex]3x+4 =25[/tex]

[tex]3x = 21[/tex]

[tex]x=7[/tex]

Please give me a brainliest answer

ACCESS MORE
EDU ACCESS
Universidad de Mexico